2019
DOI: 10.3390/ijms20040950
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Loss of the Aryl Hydrocarbon Receptor Activates Perigonadal White Fat Respiration and Brown Fat Thermogenesis via Fibroblast Growth Factor 21

Abstract: The aryl hydrocarbon receptor (AHR) is a ligand-activated transcription factor highly expressed in hepatocytes. Researchers have employed global and liver-specific conditional Ahr knockout mouse models to characterize the physiological roles of the AHR; however, the gestational timing of AHR loss in these models can complicate efforts to distinguish the direct and indirect effects of post-gestational AHR deficiency. Utilizing a novel tamoxifen-inducible AHR knockout mouse model, we analyzed the effects of hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 50 publications
3
23
0
Order By: Relevance
“…In that study, mice with high affinity for AhR were found to be more prone to obesity compared with those with low AhR affinity 9 . Other studies indicate that the AhR expression or loss of function reduces body weight and protects against problems related to a high‐fat diet 9,10,29‐32 . A recent study found significantly higher AhR and CYP1B1 gene expression in obese children compared with those with normal body weight.…”
Section: Discussionmentioning
confidence: 82%
“…In that study, mice with high affinity for AhR were found to be more prone to obesity compared with those with low AhR affinity 9 . Other studies indicate that the AhR expression or loss of function reduces body weight and protects against problems related to a high‐fat diet 9,10,29‐32 . A recent study found significantly higher AhR and CYP1B1 gene expression in obese children compared with those with normal body weight.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, the level of circulating FGF21 also increased when the protein content in the diet was low. Studies have shown that reducing protein content in diet from 25% to 10% for 4 consecutive days can increase circulating FGF21 levels by about six times (Gosby et al, 2016). Laeger et al (2014) also showed that FGF21 increased during a low protein (5% dietary protein) diet in mice and humans, even when the total energy is fixed (Bray et al, 2012).…”
Section: Fgf21 Response To Nutritional Statusmentioning
confidence: 99%
“…Stress stimulation or electrical stimulation of muscle movements caused by exercise can stimulate the phosphorylation of Akt (Ito et al, 2006; Sakamoto, Arnolds, Ekberg, Thorell, & Goodyear, 2004; Sakamoto, Aschenbach, Hirshman, & Goodyear, 2003), thus participating in the regulation of FGF21 expression. In addition, the aryl hydrocarbon receptor can constructively inhibit the transcription of FGF21 by binding to a newly identified exogenous response element in the FGF21 promoter (Girer et al, 2019). As previously mentioned, the genes related to the major signaling pathways of ER stress, such as X‐box‐binding protein 1, ATF4, and transcription factor C/EBP homologous protein, are also important activators of FGF21 transcription (Grandini, da Rocha Barros, & Navarro, 1989; Jiang et al, 2014; Montgomery et al, 2018).…”
Section: Relationship Between Exercise and Fgf21mentioning
confidence: 99%
“…Forward: 5′ ACGGCAAATTCAACGGCACAGTCA 3′, Reverse: 5′ CATTGGGGGTAGGAACACGGAAGG 3′. Protein analyses were conducted as previously described (Girer et al, 2019) Quantification of protein expression, normalized to Actin, was performed using ImageJ software (Schneider et al, 2012).…”
Section: Gapdhmentioning
confidence: 99%